ANALISIS PENGARUH PERSEPSI KUALITAS PELAYANAN DAN PERCEIVED VALUE TERHADAP KEPUASAM RELIGIUS UNTUK MENINGKATKAN MINAT MENABUNG ULANG (STUDI PADA BNI SYARIAH SEMARANG) - Al Kanzu, Hibba; Soesanto, Harry (Diponegoro Journal of Management, 2016)
The problem in this research is a decrease in the amount of third party funds (savings) are decreased and the high number of closing the savings account of Islamic banking. This research aims to test the power of perceived service quality and perceived value to religious satisfaction to improve consumer resaving interest in an Islamic Banking in semarang (study in BNI Syariah). This study using three independent variable is perceived service quality and perceived value , variable resaving intention consumer as a dependent variable and variable religious satisfaction as intervening.A method of this research technique using probability sample that is random sampling and clusters of sampling to sample as many as 100 of respondents in the middle class and over who had bought an apartment in semarang .A method of data analyst using a technique double regression analysis , the analysis includes: test the validity of , a test of reliability , test the assumption of the classics , linear regression test doublet test , test f , test the coefficients determined and test sobel.The results show significant and positive effect perceived service quality to religious satisfaction and resaving intention, significant and positive effect perceived value to religious satisfaction and repurchase intention, and then significant and positive effect religious satisfaction to repurchase intention.